Thực trạng triển khai các chương trình liên kết quốc tế bậc đại học và sau đại học tại Đại học Quốc gia Thành phố Hồ Chí Minh - Lê , Văn Hinh (Tạp chí Giáo dục, 2024)
In the context of the trend of studying abroad becoming saturated, countries that often export students and trainees, mainly developing countries, have been realizing the importance of international educational cooperation to attract domestic students and trainees. Thereby, domestic establishments can train their own human resources, solve the shortage of skills to avoid brain drain and limit investment money for education poured abroad. In Vietnam, the Ministry of Education and Training also identifies training links and international cooperation as one of the important tasks to innovate and develop the country's higher education. With the number of joint programs, Ho Chi Minh City National University is considered to play a key role in joint programs in the southern region of Vietnam. This article presents the current situation of international joint programs being implemented in Ho Chi Minh City National University system, thereby evaluating and proposing recommendations to improve program quality. The research results will contribute to the practical basis of research related to international joint programs at the undergraduate and graduate levels. At the same time, it is a reference source for planners in making appropriate and joint effective training policies.